Challenges and opportunities in agrometeorology - Attri, S. D. (Springer, 2011)
The global food security and sustainable agriculture are the key challenges before the scientific community in the present era of enhanced climate variability, rapidly rising population and dwindling resources. No part of the world is immune from meteorological extremes of one sort or another posing threat to the food security. Agrometeorology has to make most efficient use of the opportunities available in achieving the objectives of enhancing productivity and maintenance of sustainability. Increased awareness and technological advancement have provided opportunities to develop efficient agrometeorological services that can help cope with risks. These include improvements in weather forecasting, better understanding of the monsoon variability and crop-weather relationships, advances in operational agrometeorology and agrometeorological information systems, adaptation strategies to climate change and improved risk evaluation and management. This book based on an International Workshop held in New Delhi, India should be of interest to all organizations and agencies interested in agrometeorological applications.